A proposal for a technological surveillance unit aimed at regional competitiveness (2017)
Knowing and monitoring the market environment and global technological trends can contribute to better decision making in competitive intelligence. This research proposes the design of a technological surveillance unit for the construction materials sector of the department of Sucre, Colombia, through the identification of technological gaps and reference models. The research was developed methodologically through the development of a theoretical framework for reviewing scientific literature, diagnosis and identification of technological gaps in the sector and subsectors through semi-structured interviews and direct observation, the design of the surveillance unit through the needs captured from the sector and a proposal of structure and governance for the actors involved in the process. An intentional sample of 21 companies from the different subsectors of the construction materials sector was taken, revealing as results technological gaps in each of them and absence of R&D& I processes in most organizations.